Evolução do material lenhoso de pinheiro bravo e eucalipto - Louro, Graça (2011)
The present work describes and analyzes the recent evolution of wood production from maritime pine (Pinus pinaster Aiton) and eucalyptus (Eucalyptus sp.) in a context that takes in account their potentiality to supply raw material for wood base industries. The improvements, from nineteen century to present time, on the methodologies associated with land inventories, with emphasis on national forest inventories, are also described, as well as the time series results for areas, volumes and annual increments, published in the scope of national forest inventories. The evolution of these parameters shows that, in the future, the availability of wood produced on national forests is largely dependent on the increase of forest productivity. To accomplish this objective the necessary actions will involve the increment of forest active management, genetic improvement and better allocation of forest species with higher potential for wood production, namely of maritime pine and eucalyptus